A Tandem Oligonucleotide Approach for SNP-Selective RNA Degradation Using Modified Antisense Oligonucleotides. - Dorota Magner; Ewa Biala; Jolanta Lisowiec-Wachnicka; Elzbieta Kierzek; Ryszard Kierzek (PLoS ONE, 2015)
Antisense oligonucleotides have been studied for many years as a tool for gene silencing. One of the most difficult cases of selective RNA silencing involves the alleles of single nucleotide polymorphisms, in which the allele sequence is differentiated by a single nucleotide. A new approach to improve the performance of allele selectivity for antisense oligonucleotides is proposed. It is based on the simultaneous application of two oligonucleotides. One is complementary to the mutated form of the targeted RNA and is able to activate RNase H to cleave the RNA. The other oligonucleotide, which is complementary to the wild type allele of the targeted RNA, is able to inhibit RNase H cleavage. Five types of SNPs, C/G, G/C, G/A, A/G, and C/U, were analyzed within the sequence context of genes associated with neurodegenerative disorders such as Alzheimer's disease, Parkinson's disease, ALS (Amyotrophic Lateral Sclerosis), and Machado-Joseph disease. For most analyzed cases, the application of the tandem approach increased allele-selective RNA degradation 1.5-15 fold relative to the use of a single antisense oligonucleotide. The presented study proves that differentiation between single substitution is highly dependent on the nature of the SNP and surrounding nucleotides. These variables are crucial for determining the proper length of the inhibitor antisense oligonucleotide. In the tandem approach, the comparison of thermodynamic stability of the favorable duplexes WT RNA-inhibitor and Mut RNA-gapmer with the other possible duplexes allows for the evaluation of chances for the allele-selective degradation of RNA. A larger difference in thermodynamic stability between favorable duplexes and those that could possibly form, usually results in the better allele selectivity of RNA degradation.